Ivermectin biotransformation and impact on transcriptome in Arabidopsis thaliana - Syslová, Eliška; Landa, Přemysl; Navrátilová, Martina; Stuchlíková, Lucie Raisová; Matoušková, Petra; Skálová, Lenka; Szotáková, Barbora; Vaněk, Tomáš; Podlipná, Radka (Chemosphere, 2019)
Veterinary drugs enter the environment in many ways and may affect non-target organisms, including plants. The present project was focused on the biotransformation of ivermectin (IVM), one of the mostly used anthelmintics, in the model plant Arabidopsis thaliana. Our results certified the ability of plants to uptake IVM by roots and translocate it to the aboveground parts. Using UHPLC-MS/MS, six metabolites in roots and only the parent drug in rosettes were found after 24- and 72-h incubation of A. thaliana with IVM. The metabolites were formed only via hydroxylation and demethylation, with no IVM conjugates detected. Although IVM did not induce changes in the activity of antioxidant enzymes in A. thaliana rosettes, the expression of genes was significantly affected. Surprisingly, a higher number of transcripts, 300 and 438, respectively, was dysregulated in the rosettes than in roots. The significantly affected genes play role in response to salt, osmotic and water deprivation stress, in response to pathogens and in ion homeostasis. We hypothesize that the above described changes in gene transcription in A. thaliana resulted from disrupted ionic homeostasis caused by certain ionophore properties of IVM. Our results underlined the negative impact of IVM presence in the environment.
Keywords: biotransformace; kořeny rostlin; Biotransformation; Metabolites; Transcriptomic response; Veterinary drug; Arabidopsis thaliana; tandemová hmotnostní spektrometrie; Anthelmintics; Ivermectin; anthelmintika; Plant Roots; Tandem Mass Spectrometry; ivermektin; Transcriptome; Arabidopsis; transkriptom